Dental Caries Experience in Children in Public Kindergartens of Sarajevo, Bosnia and Herzegovina - Elmedin Bajrić; Amra Arslanagić; Amila Zukanović; Damir Duratbegović; Lejla Šačić-Selmanović; Elma Katana; Nina Marković (University of Zagreb. School of Dental Medicine, 2023)
Objectives: Dental caries first occurs within primary dentition in toddlers and preschool children, in a form of early childhood caries (ECC). In every day's busy and employment burdened parenting, caretakers and institutions have become important even more nowadays, not only for forming child general behavior and character, but also for maintenance of their general and oral health as well. Aims: To evaluate the presence and severity of ECC in children who attended public kindergartens in Sarajevo, and to offer basic information for the maintenance and improvement of child oral health to their parents and kindergarten teachers. Methods: The study included 1722 preschool children aged 3-6 years who attended kindergartens within Sarajevo public kindergarten institution, together with their parents and kindergarten teachers. Dental team members gradually visited all kindergartens situated in four Sarajevo city municipalities and examined kindergarten children according to the WHO Oral Health Survey Manual. Oral health promotion material for parents and kindergarten teachers was also distributed simultaneously during sequential visits. Results: ECC was present in preschool kindergarten children in Sarajevo, with its high prevalence (67.71%), dmft-value (3.97) and severity (SiC index 8.79). There was also a significant lack of dental healthcare to examined children mostly related to lack of visiting dental offices by children's parents (CI=10.55%, RI=10.80%, TI=12.98%). Conclusion: Parental role in preserving and improving of their children oral health should be systematically and profoundly improved. Kindergarten officials and staff should recognize the importance of anticariogenic diet menus and oral hygiene maintenance within their institutions.